Trauma team leaders in Canada: A national survey. (April 2020) - Belhumeur, Vincent; Malo, Christian; Nadeau, Alexandra; Hegg-Deloye, Sandrine; Gagné, Anne-Julie; Émond, Marcel
Introduction: The availability, composition and activation criteria for trauma teams vary across different health care systems, but little is known about these features in the Canadian health system. The aim of this study is to provide a description of the current trauma team available in Level 1 and 2 centres across Canada. Methods: In 2017, using a modified Dillman technique, a survey was sent to 210 health professionals across all Canadian trauma care facilities, including questions that focused on (1) the presence and the composition of a trauma team, (2) the established criteria to activate this team and (3) the initial patient care. Results: Overall, 107 (57%) completed surveys were received. Only 22 (11.7%) were from Level 1 or 2 centre and considered for compilation. Seventeen respondents have a trauma team in their centre, and they all shared their criteria for activating their team (1–27 different indications). The suspected injuries, the judgment of the emergency physician, the systolic blood pressure, the Glasgow Coma Score and the respiratory rate were the most frequently mentioned items. In the presence of a pre-hospital care warning, the initial assessment of a severely injured patient is exclusively completed by a member of the trauma team for only 35.1% of the respondents. For 11.8% of respondents, trauma team coordinates airway management. For 64.7% of participants, the trauma team leader is the dedicated care provider to accompany patients until the final destination. Conclusions: The results suggest a great variability across Canada, regarding the roles assumed by the trauma team but also regarding the activation criteria leading them to take action.